Ecologia integral e sinais dos tempos - Sleutjes, Luiz Albertus (2018)
Pope Francis, in the Encyclical Laudato Si, assumes a position of those who want to promote dialogue with all those who struggle and engage in caring for Mother Earth, one of the signs of the times, in order to solve the challenges of both social order and of ecological order. Thus, to rethink the theology of creation in its entirety is intended to combat an excluding model acquired by nations over time, especially in the last three decades. This exclusion generates more and more hostility in the common house. Starting from these presuppositions, this work aims to establish a theological reflection on the christian practice and at the same time to offer a theological-ethical collaboration, starting from the dialogue with other knowledge; therefore, it is a question of presenting the coordinates of an ecology that integrates efforts in the political, philosophical and economic field, in the light of the signs of the times. The problematic of this work is based on the following question: What are the theological and pastoral ramifications of Laudato Si in relation to ecclesial conversion and its contribution in the elaboration of ethical proposals to society? To this end, the assumed hypothesis is based on the assumption that the Encyclical Laudato Si contributes both to ecclesiological conversion and to the presentation of ethical principles and attitudes that promote social justice. These proposals go beyond those put forward by the UN, at the conclusion of the Climate Conferences or also called Conferences between the Parties (COPs). Therefore, the research is in the line of theological reflection on Christian practice, moral theology, from an eco-theology. The general objective of this work is to present the limits and possibilities of the dialogue between the integral ecology of Laudato Si and the aspirations of contemporary society in COPs 20 and 21. As specific objectives are: to contemplate reality in its challenges and impulses. In a second moment, discern how society is organized: politics; how one thinks this question: philosophy and the way in which things are produced and consumed: the economy. Finally, propose some reactions that aim to promote the integrality, care and cultivation of life: a celebration to change the look, a prayer for conversion. This research assumes as methodology the bibliographic research coming from different authors, (final considerations) in order to think the reality in the light of the interdependence of the knowledge with a view to finding solutions that are collective. Sustaining the life of everything and everyone depends on reviewing the conduct of this generation to care for and guard the common home in a healthy way and deliver it to the next generations